Influences of PZT addition on phase formation and magnetic properties of perovskite Pb(Fe0.5Nb0.5)O3-based ceramics - Amonpattaratkit,P. (Elsevier, 2015)
© 2015 Elsevier B.V. All rights reserved. In this work, the investigation of phase formation, crystal structure, microstructure, microchemical composition and magnetic properties of perovskite (1-x)PFN-xPZT (x=0.1-0.5) multiferroic ceramics derived from a combination of perovskite stabilizer PZT and a wolframite-type FeNbO4 B-site precursor was carried out by using a combination of X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) analyzer and vibrating sample magnetometer (VSM) techniques. The addition of PZT phase and its concentration have been found to have pronounced effects on the perovskite phase formation, densification, grain growth and magnetic properties of the sintered ceramics. XRD spectra from these ceramics reveal transformation of the (pseudo) cubic into the tetragonal perovskite structure. When increasing PZT content, the degree of perovskite phase formation and the tetragonality value of the ceramics increase gradually accompanied with the variation of cell volume, the M-H hysteresis loops, however, become narrower accompanied by the decrease of maximum magnetization (Mmax), remanent polarization (Mr), and coercive field (HC).